Hot wastewater recovery by using ceramic membrane ultrafiltration and its reusability in textile industry. (10th January 2018) - Dilaver, Mehmet; Hocaoğlu, Selda Murat; Soydemir, Gülfem; Dursun, Mehtap; Keskinler, Bülent; Koyuncu, İsmail; Ağtaş, Meltem
Abstract: Ceramic membrane filtration is a viable option for recovery of hot discharges due to their high mechanical, chemical and thermal durability. Recovery of hot discharges in textile industry with this method has not been studied in detail previously. In this study, the potential recovery of hot textile wastewater discharges was assessed in situ taking into consideration the amount, pollutant content and costs of the water. Samples were selected from potential recovery points according to wastewater amount, temperature and accessibility and were evaluated using laboratory scale ceramic membrane filtration with four different MWCO (300 kDa, 50 kDa, 15 kDa and 3 kDa) membrane sizes. The pollutant size distribution correlated with removal efficiency of the method and the highest pollutant removal efficiency was achieved with the 3 kDa ceramic membrane. However, the mixed hot wastewater and disperse printing washing baths mix permeate from the 3 kDa membrane had high COD and TOC contents and was not optimal for reuse without additional treatment. The printing washing baths hot discharges mix was the most appropriate option for reuse with 67 ± 12 mg COD/L, 21 ± 4 mg TOC/L and 23 ± 7.7 mg CaCO3 /L Total Hardness values which could be reused in dense dyeing and printing baths washing after 3 kDa ceramic membrane ultrafiltration. In order to define the fouling mechanism, resistance-in-series model was used and physically removable resistance was the main contributor to overall fouling. With this method, not only the reuse requirements will be met but also 22% of total water consumption may be reused and thus wastewater, energy and water related expenses may be reduced significantly in textile industry. Highlights: Ceramic membrane ultrafiltration may be a good alternative for hot wastewater recovery. Printing baths hot discharges may use as hot water after ceramic membrane filtration. The smaller MWCO of ceramic membranes showed the highest removal efficiencies. Hot water reuse may contribute to water and energy saving. Physically removable cake resistance is the dominant fouling mechanism.